Model-based techniques for virtual sensing of longitudinal flight parameters - Hardier, Georges; Seren, Cédric; Ezerzere, Pierre (Zielona Góra: Uniwersytet Zielonogórski)
Introduction of fly-by-wire and increasing levels of automation significantly improve the safety of civil aircraft, and result in advanced capabilities for detecting, protecting and optimizing A/C guidance and control. However, this higher complexity requires the availability of some key flight parameters to be extended. Hence, the monitoring and consolidation of those signals is a significant issue, usually achieved via many functionally redundant sensors to extend the way those parameters are measured.
Keywords: model-based estimation; fault detection; virtual sensor; Kalman filtering; surrogate modeling